幼児のジャンケンテストにおける選択反応時間の条件間差および年代差 - 横谷, 智久; 野口, 雄慶 (体育測定評価研究, 2015)
This study examines the experimental procedure and age differences in preschool children's choice reaction time in the game of rock-paper-scissors. Subjects included 80 healthy preschool children (aged 4 years: n = 14, 5 years: n = 48, 6 years: n = 18). To measure their choice reaction time, we made a measuring device utilizing the game of rock-paper-scissors, and measured their response time of selecting and pressing the correct answer button by the dominant hand in each condition (“draw" or “win"). The intraclass correlation coefficient (ICC) between trials was over 0.65. The two-way ANOVA indicated that the response time of all four, five, and six-year-old children was much faster, when “draw" rather than when “win" was selected. In addition, results showed that when “win" was selected, the response time of six-year-old children was substantially faster than that of four-year-old children. The reliability of the testing method developed in this study was sufficient; it was clarified that the performance of win condition improved with age.